Variasi Bahasa Anak pada Perkawinan Campur Buton Cia-Cia Laporo dan Banjar - Muhammad Andri Jambia; Asnan Hefni; Yusak Hudiyono (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aimed to examine the variation in children's language in mixed marriages between Buton Cia-Cia Laporo and Banjar in Samarinda City. The research method uses qualitative methods. The research location is in Sungai Dama Village, Samarinda City. Data collection techniques in the form of observation, documents, and interviews. Data collection, reduction, presentation, analysis, and concluding are data analysis techniques. The study results can be classified based on the language variation of children in mixed marriages, Buton Cia-Cia Laporo and Banjar. First, the speaker aspect consists of: (1) dialect; (2) idiolect; and (3) sociolect, which includes colloquial and the use of variations of Indonesian and Butonese Cia-Cia Laporo with the influence of Banjarese dialects. Second, the formal aspect consists of (1) casual variety, (2) familiar variety, and (3) the variety of businesses, and generally, the children use the Butonese Cia-Cia Laporo and Banjar languages. The three aspects of use consist of (1) the field of education; (2) the health sector in the form of a series of vocabulary, phrases and acronyms. Fourth, the aspect of facilities is a variety of spoken language characterized by non-linguistic elements.